2020
DOI: 10.1002/hbm.24994
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy and spatial properties of distributed magnetic source imaging techniques in the investigation of focal epilepsy patients

Abstract: Source localization of interictal epileptiform discharges (IEDs) is clinically useful in the presurgical workup of epilepsy patients. We aimed to compare the performance of four different distributed magnetic source imaging (dMSI) approaches: Minimum norm estimate (MNE), dynamic statistical parametric mapping (dSPM), standardized low‐resolution electromagnetic tomography (sLORETA), and coherent maximum entropy on the mean (cMEM). We also evaluated whether a simple average of maps obtained from multiple inverse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
37
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 38 publications
(40 citation statements)
references
References 86 publications
(145 reference statements)
2
37
0
Order By: Relevance
“…While fitting the data through relative entropy maximization, MEM has the unique ability to switch off parcels of the model considered as inactive using a hidden variable. In our previous studies in the context of EEG/MEG source imaging, we have demonstrated excellent accuracy of MEM and the ability to be sensitive to the spatial extent of the underlying generators (Chowdhury et al, 2013;Chowdhury et al, 2016;Grova et al, 2016;Hedrich et al, 2017;Heers et al, 2016;Pellegrino et al, 2020), before adapting this framework in the context of NIROT (Cai et al, 2021). As the most conventional inverse procedure considered in NIROT, MNE is a linear method (Hämäläinen & Ilmoniemi, 1994) using Tikhonov regularization to minimize the L2-norm.…”
Section: Nirot Reconstructionmentioning
confidence: 99%
“…While fitting the data through relative entropy maximization, MEM has the unique ability to switch off parcels of the model considered as inactive using a hidden variable. In our previous studies in the context of EEG/MEG source imaging, we have demonstrated excellent accuracy of MEM and the ability to be sensitive to the spatial extent of the underlying generators (Chowdhury et al, 2013;Chowdhury et al, 2016;Grova et al, 2016;Hedrich et al, 2017;Heers et al, 2016;Pellegrino et al, 2020), before adapting this framework in the context of NIROT (Cai et al, 2021). As the most conventional inverse procedure considered in NIROT, MNE is a linear method (Hämäläinen & Ilmoniemi, 1994) using Tikhonov regularization to minimize the L2-norm.…”
Section: Nirot Reconstructionmentioning
confidence: 99%
“…3, Table .1 and supplementary section S2), we found that MNE overall reconstructed well the main generator but largely overestimated the size of the underlying generator. MEM was specifically developed, in the context of EEG/MEG source imaging, as a method able to recover the spatial extent of the underlying generators, which has been proved not to be the case for MNE-based approaches (Chowdhury et al, 2013(Chowdhury et al, , 2016Grova et al, 2016;Hedrich et al, 2017;Pellegrino et al, 2020). A recent review (Sohrabpour and He, 2021) in the context of EEG/MEG source imaging has also demonstrated that the Bayesian approach with sparsity constraints is required to accurately estimate the spatial extent.…”
Section: Spatial Accuracy Of 3d Fnirs Reconstruction Using Memmentioning
confidence: 99%
“…The MEM framework was specifically designed and evaluated for its ability to recover spatially extended generators (Heers et al, 2016;Pellegrino et al, 2016;Chowdhury et al, 2016;Grova et al, 2016). We recently demonstrated its excellent performances when dealing with focal sources (Hedrich et al, 2017) and when applied on clinical epilepsy data (Chowdhury et al, 2018;Pellegrino et al, 2020). In addition to its unique ability to recover the spatial extent of the underlying generators, we also demonstrated MEM's excellent accuracy in low SNR conditions, with the ability to limit the influence of distant spurious sources (Chowdhury et al, 2016;Hedrich et al, 2017;Heers et al, 2016;Pellegrino et al, 2020;von Ellenrieder et al, 2016;Aydin et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, it makes use of non-convex sparsity priors and joint inference of source estimates to obtain accurate source amplitudes. Various applications for MEG/EEG source reconstruction have been applied in the clinical setting for detection of epileptic spikes [ 28 ], identification of seizure onset zone [ 29 ] and presurgical workup of epilepsy patients [ 30 , 31 , 32 ].…”
Section: Introductionmentioning
confidence: 99%